Postexposure‐vaccine‐prophylaxis against COVID‐19. Issue 1 (11th November 2022) - Shmuelian, Zohar; Warszawer, Yehuda; Or, Omri; Arbel‐Alon, Sagit; Giladi, Hilla; Avgil Tsadok, Meytal; Cohen, Roy; Shefer, Galit; Shlomi, Dekel; Hoshen, Moshe; Maruotti, Antonello; Jona‐Lasinio, Giovanna; et al.
Abstract: During the COVID‐19 pandemic, postexposure‐vaccine‐prophylaxis is not a practice. Following exposure, only patient isolation is imposed. Moreover, no therapeutic prevention approach is applied. We asked whether evidence exists for reduced mortality rate following postexposure‐vaccine‐prophylaxis. To estimate the effectiveness of postexposure‐vaccine‐prophylaxis, we obtained data from the Israeli Ministry of Health registry. The study population consisted of Israeli residents aged 12 years and older, identified for the first time as PCR‐positive for SARS‐CoV‐2, between December 20th, 2020 (the beginning of the vaccination campaign) and October 7th, 2021. We compared "recently injected" patients—that proved PCR‐positive on the same day or on 1 of the 5 consecutive days after first vaccination (representing an unintended postexposure‐vaccine‐prophylaxis)s—to unvaccinated control group. Among Israeli residents identified PCR‐positive for SARS‐CoV‐2, 11 687 were found positive on the day they received their first vaccine injection (BNT162b2) or on 1 of the 5 days thereafter. In patients over 65 years, 143 deaths occurred among 1412 recently injected (10.13%) compared to 255 deaths among the 1412 unvaccinated (18.06%), odd ratio (OR) 0.51 (95% confidence interval [CI]: 0.41–0.64; p < 0.001). A significant reduction in the death toll was observed among the 55–64 age group, with 8 deaths occurring among the 1320 recently injected (0.61%) compared to 24 deaths among the 1320 unvaccinated control (1.82%), OR 0.33 (95% CI: 0.13–0.76; p = 0.007). Postexposure‐vaccine‐prophylaxis is effective against death in COVID‐19 infection.